The Descent of Pluto: Interactive dynamics, specialisation and reciprocity of roles in a Wikipedia debate. Issue 86 (February 2016) - Détienne, Françoise; Baker, Michael; Fréard, Dominique; Barcellini, Flore; Denis, Alexandre; Quignard, Matthieu
Abstract: This research focuses on analysing collective activity in Wikipedia, conceptualised as an Online Epistemic Community ("OEC"). Previous research on Wikipedia has shown that widespread participation, coupled with the principle of neutrality of viewpoint, has led to 'editing wars' and associated high coordination costs. The question that we address is therefore that of how to analyse the interactive dynamics of conflictual OEC discussions. To address this issue, we performed a longitudinal analysis of a specific case-study within the French-speaking "astronomy" Wikipedia OEC, revolving around the renaming of the article on the celestial body "Pluto", given the 'descent' of its scientific status from that of a planet to an asteroid. Our choice was to focus on the analysis of dialogic and epistemic roles, as an appropriate meso-level unit of analysis. We present a qualitative-quantitative method for analysis of roles, based on filtering major participants and analysing the dialogic functions and epistemic contents of their communicative acts. Our analyses showed that online epistemic communities can be communities in the true sense of their involving cooperation, in that roles become gradually specialised and reciprocal over sequences of the discussion: when one participant changes role from one sequence to another, other participants 'fill in' for the vacant role. Secondly, we show that OECs, in the case of Wikipedia, do not function purely on a knowledge-level, but also involve, crucially, negotiation of images of participants' competences with respect to the knowledge domain. In that sense, OECs can be seen as socio-cognitive communities. The originality of our research resides in the qualitative-quantitative method for analysing interactive roles, and the results of its application to an extended longitudinal case study. Highlights: We develop a methodology for qualitative-quantitative analysis of interactive roles in Online Epistemic Communities (OECs). We show how interactive roles are reciprocal and symmetrical in OECs. We show that OECs involve both knowledge-based and interpersonal processes (negotiation of images of participants' competences).